The CEO beauty premium: Founder CEO attractiveness and firm valuation in initial coin offerings. (20th January 2022) - Colombo, Massimo G.; Fisch, Christian; Momtaz, Paul P.; Vismara, Silvio
Abstract: Research summary: We apply insights from research in social psychology and labor economics to the domain of entrepreneurial finance and investigate how founder chief executive officers' (founder CEOs') facial attractiveness influences firm valuation. Leveraging the novel context of initial coin offerings (ICOs), we document a pronounced founder CEO beauty premium, with a positive relationship between founder CEO attractiveness and firm valuation. We find only very limited evidence of stereotype‐based evaluations, through the association of founder CEO attractiveness with latent traits such as competence, intelligence, likeability, or trustworthiness. Rather, attractiveness seems to bear economic value per se, especially in a context in which investors base their decisions on a limited information set. Indeed, attractiveness has a sustainable effect on post‐ICO performance. Managerial summary: ICOs allow ventures to collect funding from investors using blockchain technology. We leverage this novel funding context, in which information on the ventures and their future prospects is scarce, to empirically investigate whether the founder CEOs' physical attractiveness is associated with increased funding (i.e., amount raised) and post‐funding performance (i.e., buy‐and‐hold returns). We find that ventures with more attractive founder CEOs outperform ventures with less attractive CEOs in both dimensions. For ICO investors, this suggests that ICOs of firms with more attractive founder CEOs are more appealing investment targets. Our findings are also interesting for startups seeking external finance in uncertain contexts, such as ICOs. If startups can appoint attractive leaders, they may have better access to growth capital.